2018
DOI: 10.29359/bjhpa.10.2.04
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regular aerobic exercises on premenstrual syndrome in sedentary women

Abstract: Background: Premenstrual symptoms (PMS) occur very commonly and cause a negative impact on the overall quality of women's lives. The aim of this study was to assess the PMS symptoms between women who exercise and non-exercising sedentary women. Material and methods:A total of 220 participants were studied. N = 100 exercising group and N = 120 non-exercising were selected as participants. The exercising group was selected from women who regularly do aerobic exercise (walk-running) for 3−5 days a week, within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…They found that PMS rates were lower in those who had normal physical activity dail. In some studies were reported that regularly, moderate aerobic exercise reduced PMS symptoms and could be used as a treatment method [8,10,11]. Baat et al [9] also determined to regular aerobic exercise positive effect on PMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that PMS rates were lower in those who had normal physical activity dail. In some studies were reported that regularly, moderate aerobic exercise reduced PMS symptoms and could be used as a treatment method [8,10,11]. Baat et al [9] also determined to regular aerobic exercise positive effect on PMS.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies, 30 minutes of aerobic exercise is recommended for at least 3 days per week to contribute to the regulation of both body composition, mood and to improve physical symptoms [8,9]. Also some studies recommend for 60 minutes of aerobic exercise [10,11]. In addition, balanced diet, reduction of salt, caffeine and refined sugar intake, restricted high and saturated fat, increasing the consumption of omega-3, magnesium, zinc, vitamins B and E are effective in reducing PMS symptoms [1,6,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding psychological symptoms, women who did not exercise had more difficulty concentrating. This difference may be associated with the ability of exercise to increase adrenal cortisol levels, which aids concentration and balances mood changes and thus improves focus (Cicek, 2018;Virk et al, 2019;Abebe et al, 2019), especially during regular activities, which generates positive effects on both attention and academic performance. For university students, this effect is relevant to academic performance because concentration in school leads to better understanding of the studied subjects, thus generating high grades in evaluative activities and self-confidence among students (De Greeff et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, physical exercise improves cardiovascular activity and, consequently, oxygenation (Virk et al, 2019), delaying symptoms of fatigue. In addition, the endorphins produced during physical exercise have a relaxing effect, which is another reason why physically active women do not feel as fatigued as women who do not exercise (Cicek, 2018;Yilmaz-Akyuz and Aydin-Kartal, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic aerobic exercise recommended as a method to reduce PMS occurrence and severity. Recommended aerobic exercise, in particular to reduce fatigue and depression associated with PMS [12]. The U.S department of health and human services recommends regular aerobic activity as treatment for PMS.…”
Section: Introductionmentioning
confidence: 99%